The optimal timing of outpatient Biobrane™ application for superficial and mid dermal partial thickness burns: Evidence for the '12-hour rule'. Issue 4 (June 2019) - Harish, Varun; Li, Zhe; Maitz, Peter K.M.
Highlights: Treating superficial and mid dermal burn wounds with Biobrane™ within 12 h of the burn leads to a statistically significant 63% reduction in healing time. Benefits are seen independent of the burn mechanism, body surface area of the burn injury, the patient's age, and the adequacy of first aid. First study in the literature to provide an evidence base for the optimal timing of Biobrane™ application — the '12-hour rule'. Abstract: Background: Biobrane™ is a skin substitute used for the definitive management of partial thickness burns. No studies have examined the optimal timing of Biobrane™ application in this setting. The purpose of this study was to determine whether there was a clinically significant difference in applying Biobrane to a superficial and mid dermal partial thickness burn within 12 h after burn. Methods: From August 2016–February 2017, 29 consecutive superficial and mid dermal partial thickness burn injuries were prospectively treated with Biobrane™ within 12 h of the injury. This 'early Biobrane™' cohort was compared to a historical cohort of 148 patients who were treated with Biobrane™ for superficial and mid dermal burns after 12 h after injury during 2015 to 2016. Multivariate regression analysis was used to determine the difference in time to re-epithelialisation and number of outpatient visits between the two cohorts. Results: In the 'early Biobrane™' group, the mean TBSA was 3.5 ± 2.7%. and the mean time to Biobrane™ application was 7.1 ± 2.7 h after burn injury. The mean time to re-epithelialisation in this group was 9.1 ± 3.0 days, and no patients underwent skin grafting. In the 'delayed Biobrane™' group, the mean TBSA was 2.6 ± 2.8% and the mean time to Biobrane™ application was 35.1 ± 21.4 h. The mean time to re-epithelialisation was 14.8 ± 8.7 days, with 3 patients undergoing skin grafting. Regression analysis demonstrated a statistically significant 63% reduction in time to re-epithelialisation (95% CI = 0.23–0.60; P < 0.0001) with early Biobrane™ application. Conclusion: Patients treated with application of Biobrane™ within 12 h of superficial and mid dermal partial thickness burns have a statistically significant reduction in healing time when compared to patients treated with standard Biobrane™ practice.